Analysis of BPJS Ketenagakerjaan's Responsibility in Protecting Employee Rights at PTPN IV Panai Jaya Company - Dara Nabila; Rahmi Syahriza; Tri Inda Fadhila Rahma (International Journal of Multi Discipline Science (IJ-MDS), 2025)
This study aims to analyse the implementation of the Social Security Administering Agency (BPJS) Ketenagakerjaan's responsibilities in protecting workers' rights at the state-owned agribusiness company, PTPN IV Panai Jaya. This study used a descriptive qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews with 6 informants, consisting of employees, company officials, and BPJS officers, as well as internal company observations and documentation. Data analysis was carried out through content analysis, which aims to interpret the meaning of qualitative data systematically and objectively. The results of this study indicated that the implementation of BPJS Ketenagakerjaan’s responsibility in protecting workers' rights at PTPN IV Panai Jaya was still not optimal, especially in reaching non-permanent workers such as casual daily workers and contract workers. Although all permanent employees had received benefits from social security programs such as JKK, JKM, JHT, and JKP, the majority of non-permanent workers had not enjoyed the same protection. This indicates a gap between formal social security coverage and functional realisation in the field. In addition, several permanent workers were also found unable to use their BPJS Ketenagakerjaan insurance because PTPN IV Panai Jaya delayed payment of BPJS contributions.